2021
DOI: 10.1556/650.2021.32169
|View full text |Cite
|
Sign up to set email alerts
|

A szorongás és a diabetes közti kapcsolat

Abstract: Összefoglaló. A cukorbetegség és a depresszió kapcsolatáról számos tanulmány született. A szorongás és a diabetes közti összefüggést már kevesebben vizsgálták, pedig jelentős szerepük van a szorongásos kórképeknek is, hiszen nagyon gyakori a két betegség együttes előfordulása. A diabetes már önmagában is nagy betegségterhet jelent a betegek számára, a társuló pszichiátriai kórképek pedig tovább rontják a kezelés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The affective temperament model was developed based on clinical and scienti c observations of affective disorder patients and their unaffected rst-degree relatives, and have been validated in several clinical, theoretical, and molecular studies [2][3][4][5][6]. Although they have no pathological value in themselves, affective temperaments represent vulnerability factors for the development of various psychiatric [7,8] and somatic conditions [9][10][11][12][13][14][15][16][17][18][19][20], and potentially affect the long-term course and treatment outcome of these conditions [7,16,18,21] either directly, via shared biological background factors, or indirectly, by in uencing emotions, cognitions and behaviours which may have an effect either on the development or the treatment of the illness [7,22].…”
Section: Introductionmentioning
confidence: 99%
“…The affective temperament model was developed based on clinical and scienti c observations of affective disorder patients and their unaffected rst-degree relatives, and have been validated in several clinical, theoretical, and molecular studies [2][3][4][5][6]. Although they have no pathological value in themselves, affective temperaments represent vulnerability factors for the development of various psychiatric [7,8] and somatic conditions [9][10][11][12][13][14][15][16][17][18][19][20], and potentially affect the long-term course and treatment outcome of these conditions [7,16,18,21] either directly, via shared biological background factors, or indirectly, by in uencing emotions, cognitions and behaviours which may have an effect either on the development or the treatment of the illness [7,22].…”
Section: Introductionmentioning
confidence: 99%
“…Affective temperaments (depressive, cyclothymic, hyperthymic, irritable, and anxious) represent vulnerability factors towards the development of various psychiatric 17,18 and somatic diseases [19][20][21][22][23][24][25][26][27][28][29][30] and affect the long-term course and treatment outcome of several of these conditions 17,26,28,31 . In a previous study, we reported that affective temperaments also affect infertility treatment success 32 , and we discussed that the necessary next step is to identify the processes and factors through which they exert their in uence, and which may be modi able with psychological interventions and patient-centered, targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Affective temperaments (depressive, cyclothymic, hyperthymic, irritable, and anxious) represent vulnerability factors towards the development of various mental disorders 20,21 and somatic diseases [22][23][24][25][26][27][28][29][30][31][32][33] and affect the longterm course and treatment outcome of several of these conditions 20,29,31,34 . Unlike other models which universally describe basic personality traits, the model of affective temperaments has been developed based on observation of affective disorder patients and their first-degree relatives and focuses on emotional reactivity and related cognitions and behaviors.…”
mentioning
confidence: 99%